2011
DOI: 10.4257/oeco.2011.1503.14
|View full text |Cite
|
Sign up to set email alerts
|

Animal Invaders in São Paulo State Reservoirs

Abstract: Freshwaters are among the most vulnerable ecosystems regarding biological invasions. Reservoirs built after the last half century in São Paulo State have been continuously subjected to the introduction and establishment of alien species, both exotic and allochtonous. Here we present a short historical and the present status of some recent, still going on, biological invasion processes, for both, invertebrate and vertebrates, with emphasis on Tietê River basin. Among reservoir communities, the zooplankton has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
18
0
7
Order By: Relevance
“…Reservoirs have been continually subject to the introduction and establishment of alien species, as reported by Rocha et al 24 in State of São Paulo. The authors showed that rapid invasion processes were ongoing on the Tietê River basin for three species of mollusks: C. fluminea, Limnoperna fortunei (Dunker, 1857) and M. tuberculata.…”
Section: Discussionmentioning
confidence: 99%
“…Reservoirs have been continually subject to the introduction and establishment of alien species, as reported by Rocha et al 24 in State of São Paulo. The authors showed that rapid invasion processes were ongoing on the Tietê River basin for three species of mollusks: C. fluminea, Limnoperna fortunei (Dunker, 1857) and M. tuberculata.…”
Section: Discussionmentioning
confidence: 99%
“…The first registers of golden mussel in the reservoir cascades of this region of La Plata were reported in the beginning of 2000's. Between 2001 and 2004 its presence was detected in the reservoirs of Ilha Solteira, Jupiá, Porto Primavera and Itaipu, upper Paraná River (Zanella and Marenda, 2002;Mansur et al, 2004;Von Ruckert et al, 2004 andAvelar et al, 2004); during 2006 in the reservoirs of Canoas I, Canoas II and Capivara, Paranapanema River (Garcia et al, 2009;Rocha et al, 2011);during 2007/2008 in Tibagi and Iguaçu Rivers (Pestana et al, 2010); during 2004 in the Tietê River (already mentioned) (Pareschi et al, 2008). In the most northern large rivers of the basin, Paranaíba and Grande Rivers, we did not register the species presence.…”
Section: Discussionmentioning
confidence: 99%
“…Deve ser salientado, que rápidos processos de invasão também estão em andamento por outras espécies de moluscos, como o bivalve asiático Corbicula fluminea e o mexilhão dourado Limnoperna fortunei (Rocha et al, 2011).…”
Section: Introductionunclassified
“…Além disso, foi uma das espécies dominantes encontrada no reservatório de Salto Grande em Americana, SP (Pamplim et al, 2005) e nas represas do médio e baixo rio Tietê (Suriani et al, 2007;Rocha et al, 2011). Com a grande ocorrência deste organismo no Brasil e especialmente no estado de São Paulo, é de grande importância fornecer informações da ocorrência e da sua distribuição espacial, sendo informações úteis para o controle da sua dispersão.…”
Section: Introductionunclassified